Pengaruh Kompensasi Finansial dan Kepuasan Kerja terhadap Kinerja Karyawan pada Toko Garden Textile Jakarta - Alvanesya Pramudita; Agus Dharmanto; Nita Komala Dewi (Jurnal Riset dan Inovasi Manajemen, 2024)
The Influence of Financial Compensation and Job Satisfaction on the Performance of Garden Textile Store Employees in Jakarta. This research aims to determine the influence of Financial Compensation and Job Satisfaction on Employee Performance at the Garden Textile Store in Jakarta. The object of this research is the Garden Textile Store, Jakarta. This research uses a quantitative approach with multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 26 application. The sampling technique in this research uses a saturated sampling technique. The sample in this research was all 40 employees of the Garden Textile Store in Jakarta. Based on the research results, it shows that the financial compensation variable has a partially significant effect on the performance of the employees of the Garden Textile Store, Jakarta, the job satisfaction variable has a partially significant effect on the performance of the employees of the Garden Textile Store, Jakarta. The research results also show that the variables of financial compensation and job satisfaction simultaneously have a significant effect on employee performance at the Garden Textile Store in Jakarta